Isolation and molecular analysis of cDNA encoding a partial endoglucanase gene from aspergillus terreus SUK-l - Nik Marzuki Sidik,; Shaiful Adzni Sharifuddin,; Othman Omar ,; Abdul Jalil Abdul Kader,; Sahidan Senafi, (Universiti Kebangsaan Malaysia, 2006)
We report here the isolation and sequence analysis of a cDNA fragment for an endoglucanase gene from Aspergillus terreus SUK-I. A pair of primers was designed based on conserved regions of endoglucanase gene. Amplification of A. terreus SUK-I cDNA using the primers produced a DNA band of 642 bp. The cDNA fragment was purified and cloned into pCR®ll-TOPO plasmid vector. The cDNA insert was designated as SA2 and sequenced. Analysis of the SA2 sequence showed a high degree of identity towards endoglucanase gene sequences from A. aculeatus, A kawachii and Talaromyces emersonii. While, the putative amino acid sequence of SA2 showed 74 % identity towards endoglucanase protein from Thermoascus aurantiacus and 69 % identity towards endoglucanase protein from A. kawachii, A. niger, A. aculeatus and A. nidulans. A 66 % identity between SA2 putative amino acid sequence and A. oryzae endoglucanase protein sequence was also observed. Therefore, we concluded that SA2 codes for a putative endoglucanase gene of A. terreus SUK-I.